A PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN SUASANA TERHADAP KEPUASAN PELANGGAN DI KOPI PODJOK MAMPANG - Chairul Nadri; Verry Cyasmoro (LPPM Universitas Asa Indonesia, 2025)
This study aims to determine the effect of product quality, service quality, and atmosphere on customer satisfaction at Kopi Podjok Mampang Prapatan. The approach used is a quantitative method with data collection techniques through distributing questionnaires to 168 respondents using accidental sampling techniques. The data obtained were analyzed using multiple linear regression analysis with the help of IBM SPSS Statistics 25 software. The results of the study indicate that service quality and atmosphere have a significant effect on customer satisfaction, while product quality does not show a significant effect. This finding indicates that good service and a comfortable shop atmosphere determine the level of customer satisfaction more than the quality of the product itself. Therefore, Kopi Podjok is advised to continue to improve the quality of service and maintain the shop atmosphere so that it remains attractive and supports positive customer experiences.